Bullous pemphigoid in an elderly patient with myelodysplastic syndrome and refractory anemia coupled with excess of blast - Lee, Y.Y.; Bee, P.C.; Lee, C.K.; Naiker, M.; Ismail, R. (2011)
Bullous pemphigoid (BP) has a recognized association with solid organ tumors, but is relatively rare in hematological malignancies. We report a 67-year-old male who developed BP after being diagnosed with myelodysplastic syndrome and refractory anemia with excess of blast (RAEB). Skin biopsy elucidated sub-epidermal bulla using direct immunofluorescence, revealing linear C3 and IgG deposits along the basement membrane. His BP was recalcitrant to the conventional treatment and only responded to a combination of high dose oral prednisolone and azathioprine. The relative refractory nature of his condition and concurrent RAEB supports a paraneoplastic nature.